Flipping the ICF: Exploring the Interplay of Theory and the Lived Experience to Reconsider Physical Activity in Community-Dwelling People With Multiple Sclerosis - Stennett, Andrea Marjorie; De Souza, Lorraine H.; Norris, Meriel (Frontiers in Rehabilitation Sciences, 2021)
People with multiple sclerosis (MS) report lower physical activity levels and are at a risk of becoming sedentary. As such, they are at an increased risk of developing secondary health conditions associated with inactivity. This is of major public health concern. Attempts to improve the physical activity levels in people with MS remain a challenge for health professionals. One key reason might be the lack of understanding about the meanings people with MS ascribe to exercise and physical activity. This paper draws on the key findings of a three-phased interconnected mixed methods sequential explanatory study to examine the meanings of exercise and physical activity from the perspectives of people with MS and health professionals. Phase 1 used a four-round Delphi questionnaire to scope and determine the consensus of priorities for exercise and physical activity and the reasons why people with MS (N = 101) engaged in these activities. Phase 2 used face-to-face semistructured interviews of people with MS (N = 16) to explore the meanings ascribed to exercise and physical activity. Phase 3 explored the perceptions of physiotherapists (N = 14) about exercise and physical activity using three focus groups. Using the International Classification of Functioning, Disability, and Health as a theoretical framework to underpin this study, the authors discuss the key factors, for example, emphasis on the contextual factors, that drive decision making around exercise and physical activity participation in people with MS and explore the clinical implications to health professionals.